2011
DOI: 10.1016/j.ajpath.2011.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Autophagic Response in Patients with Chronic Hepatitis C Virus Infection

Abstract: Autophagy is a regulated process that can be involved in the elimination of intracellular microorganisms and in antigen presentation. Some in vitro studies have shown an altered autophagic response in hepatitis C virus infected hepatocytes. The present study aimed at evaluating the autophagic process in the liver of chronic hepatitis C (CHC) patients. Fifty-six CHC patients and 47 control patients (8 with nonalcoholic steatohepatitis or alcoholic liver disease, 18 with chronic heptatitis B virus infection, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 20 publications
3
62
0
2
Order By: Relevance
“…Alcoholic cirrhosis (n = 6) (22-24), including nonalcoholic fatty liver disease (25), chronic hepatitis C infection (26), and acetaminophen toxicity (27). However, autophagy has also been shown to increase in HSC during activation (22,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholic cirrhosis (n = 6) (22-24), including nonalcoholic fatty liver disease (25), chronic hepatitis C infection (26), and acetaminophen toxicity (27). However, autophagy has also been shown to increase in HSC during activation (22,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies with similar results evaluated autophagy in patients with chronic HCV infection [69,70]. However, in experimental studies autophagy was activated in HCV-RNA expressing cultured cells [71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…67 Studies have shown that there is an accumulation of autophagic vacuoles in HCV-infected hepatocytes; however this autophagy is inefficient as the autophagosomes are not able to increase autophagic protein degradation. The strategies used by HCV to evade and take advantage of autophagy for its replication are: (i) HCV avoids recognition by the autophagic process with rare or no co-localization of HCV proteins in autophagic vacuoles [68][69][70] ;…”
Section: Targeting Autophagy In Infective Diseases: Hepatitis B Virusmentioning
confidence: 99%
“…(ii) HCV prevents maturation of autophagosomes into autolysosomes 68,69 ; and (iii) HCV utilizes components of autophagy to enhance intracellular replication. The autophagy proteins are likely to be proviral factors for the initial steps of HCV replication.…”
Section: Targeting Autophagy In Infective Diseases: Hepatitis B Virusmentioning
confidence: 99%
See 1 more Smart Citation